PERBANDINGAN BERAT LAHIR, PERSENTASE JENIS KELAMIN ANAK DAN SIFAT PROLIFIK INDUK KAMBING PERANAKAN ETAWAH PADA PARITAS PERTAMA DAN KEDUA DI KOTA METRO - Hamdani, Muhammad Dima Iqbal (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The aim of research was to compare birth weight, sex of kids, prolificacy of does between the first and second parity of Ettawa grade goat at Metro City to select replacement stock that was prolific and high at birth weight. Survey method was used in this research to observe birth weight of male and female kid, percentage of male and female kid, percentage of does foals single kid and twin, litter size between the first and second parity. Survey was conducted by observation recording of 80 heads of doe. Result of this research indicated that birth weight of male kid of the first parity (2,60 ± 0,26 kg) and the second parity (2,67 ± 0,18 kg) were higher (P<0,05) than that of female kid of the first parity (2,43± 0,21 kg) and the second parity (2,48 ± 0,15 kg), 46 % kids of the first parity and 42 % kids of the second parity were male, 54 % kids of the first parity and 58 % kids of the second parity were  female, 45 % does of the first parity and 40 % does of the second parity foal twin kids, 55 % does of the first parity and 60 % does of the second parity foal single kid, litter size of of the second parity (1,56±0,50 heads) was higher (P<0.05) than that of the first parity (1,41±0,50 heads) It could be concluded that prolificacy of does of the first and second parity were not good and kids born at the second parity and high at birth weight could be choosen as replacement stock. Key words : Birth weight, Percentage of sex, Prolific, First and Second Parity, Ettawa grade goat, Metro City.